A nationally representative study on discharge against medical advice among those living with epilepsy. (January 2021) - Agarwal, Parul; Xi, Huaqing; Jette, Nathalie; Lin, Jung-yi; Kwon, Churl-Su; Dhamoon, Mandip S.; Mazumdar, Madhu
Highlights: Around 2 % admissions in people living with epilepsy resulted in DAMA and these are more frequent in socially-disadvantaged populations. DAMA-related admissions in people with epilepsy significantly increased from 2003 to 2014. Top reasons for DAMA admissions were epilepsy/convulsions, alcohol- and substance-related disorders, and complicated diabetes mellitus. Abstract: Purpose: Discharges against medical advice (DAMA) are associated with adverse patient outcomes among those with epilepsy. Our goal was to examine trends and factors associated with DAMA among those living with epilepsy. Methods: A retrospective cross-sectional study was performed using the 2003–2014 National Inpatient Sample database. ICD-9-CM diagnosis codes were used to identify admissions of patients with epilepsy. Following outcomes were examined among epilepsy patients: proportion and predictors of DAMA, 12-year DAMA trends and causes of admissions. Results: In 2014, of the 187, 850 admissions in patients with epilepsy, 3783 (2.01 %) were DAMA. Male sex, Black race, younger age, lower household income, Medicaid/self-pay/other as primary payer, lower Elixhauser comorbidities index, weekend admission, non-elective admission, hospital in northeast region, and urban nonteaching hospital were all associated with DAMA. There was a significant increase in the proportion of DAMA in people with epilepsy from 2003 to 2014 (1.13 %–2.01 %, p < 0.0001). The top reasons of admissions for epilepsy patients who were DAMA were: epilepsy/convulsion (21.02 %), alcohol- (8.86 %) and substance-related disorders (3.75 %), and diabetes mellitus with complications (3.33 %). Conclusions: Our findings provide opportunities to understand DAMA among those living with epilepsy, which is more prevalent in socially-disadvantaged populations. This study highlight the need to develop electronic medical records-based prediction tools that could be used at the point-of-care to enable the early identification of people at risk for DAMA, since it is often likely preventable. Future mixed methods studies are recommended to identify facilitators of DAMA and strategies for prevention.